REFLEKSI KEYAKINAN CALON GURU GENERASI Z DALAM PEMBELAJARAN BAHASA DI ERA DIGITAL - Rio Rinaldi Rio; Yetty Morelent; Fauzul Bastian (Universitas Muhammadiyah Makassar, 2026)
This study aims to analyze the extent to which these beliefs influence their choices of strategies, techniques, learning materials, and assessment instruments in language teaching. The research employed a descriptive quantitative design with interpretive qualitative analysis, using an online Likert-scale questionnaire (1–5) distributed to students of the Indonesian Language and Literature Education Program at Universitas Bung Hatta. The instrument covered five domains: the role of the language teacher, teaching strategies and techniques, material selection, evaluation and assessment, and perceptions of Generation Z teachers. Findings reveal that all domains scored above 4.0, indicating high levels of pedagogical belief and confidence. Respondents preferred collaborative and project-based learning, authentic materials, and feedback-driven formative assessment. These results suggest that Generation Z pre-service teachers possess a pedagogical orientation aligned with 21st-century learning paradigms, reflecting their technological adaptability and reflective awareness as future educators in a digitalized educational landscape.